Relationship Between Middle Ear Volume and Long-term Audiological Outcomes in Congenital Aural Atresia Repair. Issue 6 (July 2019) - Imbery, Terence E.; Maldonado, Michael; Mukherjee, Sugoto; Kesser, Bradley W.
Abstract : Objective: To assess the association of middle ear volume with long-term hearing outcomes in congenital aural atresia (CAA) repair. Study Design: Retrospective chart and radiological review. Setting: Single academic tertiary referral center. Patients: Children and adults who underwent CAA repair between 1995 and 2016. Patients were divided into "best" and "worst" audiometric groups, based on stability of postoperative air conduction pure-tone average (AC PTA) results. Ten patients were included for study in the "best" group, and 12 in the "worst" group. Intervention(s): CAA repair. Main Outcome Measure(s): Long-term (> 1 yr) postoperative three-tone (500, 1000, 2000 Hz) AC PTA, speech reception threshold (SRT), air bone gap, and semiautomated calculated middle ear volume from preoperative computed tomography (CT) scans. Results: Statistically significant differences were noted between "best" and "worst" groups in AC PTA, SRT, and air bone gap ( p < 0.001). Mean middle ear volume in the "best" group was 434.6 mm 3 (range 326.3–602.1 mm 3 ) and 339.5 mm 3 (range 199.4–502.1 mm 3 ) in the "worst" group ( p = 0.02). The majority in both groups were right ears ( p = 0.38), and males outnumbered females in the "best" group (9 out of 10; p = 0.018). Preoperative Jahrsdoerfer grading scores were similar between groups ( p = 0.31). Mean follow-up for the "best" and "worst" groups was approximately 3.5 and 4.5 yr, respectively. Conclusions: For patients undergoing CAA repair, larger middle ear volume is associated with stable and better long-term audiometric outcomes.